The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/marc.202100501
|View full text |Cite
|
Sign up to set email alerts
|

Styrene‐Maleimide/Maleic Anhydride Alternating Copolymers: Recent Advances and Future Perspectives

Abstract: Alternating sequencing of styrene‐maleimide/maleic anhydride (S‐MI/MA) in the copolymer chain is known for a long time. But since early 2000, this class of copolymers has been extensively studied using various living/controlled polymerization techniques to design S‐MI/MA alternating copolymers with tunable molecular weight, narrow dispersity (Ð), and precise chain‐end functionality. The widespread diverse applications of this polymeric backbone are due to its ease of synthesis, cheap starting materials, high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 138 publications
0
24
0
1
Order By: Relevance
“…[5][6][7][8] It is estimated that the retention time of FMPs in the environment can last for hundreds of years, and their accumulation has adverse health effects on feeding, fecundity, and immune response of organisms. [9][10][11] What is worse, FMPs have one-dimensional linear structure and are prone to entanglement with various organs, allowing them to stay in intestine for a long time and difficult to be excreted. [4] Moreover, FMPs can also act as a medium or vector to transport toxic contaminants and heavy metals due to their higher specific surface area than large pieces of plastic wastes, resulting in bioaccumulation of contaminants and poisoning in aquatic life.…”
mentioning
confidence: 99%
“…[5][6][7][8] It is estimated that the retention time of FMPs in the environment can last for hundreds of years, and their accumulation has adverse health effects on feeding, fecundity, and immune response of organisms. [9][10][11] What is worse, FMPs have one-dimensional linear structure and are prone to entanglement with various organs, allowing them to stay in intestine for a long time and difficult to be excreted. [4] Moreover, FMPs can also act as a medium or vector to transport toxic contaminants and heavy metals due to their higher specific surface area than large pieces of plastic wastes, resulting in bioaccumulation of contaminants and poisoning in aquatic life.…”
mentioning
confidence: 99%
“…First, to ensure alternating arrangement of mers styrene (St) and maleic anhydride (MA), molecules were chosen as cores of the monomers for further derivatization with donor and acceptor moieties, respectively. Due to a much higher rate constant of copolymerization than the respective rate constants of homopolymerization processes, St and MA tend to form alternating copolymers [45]. Because of its electron-donating character, St was coupled with the selected donor side group, thiophene, by means of Suzuki reaction giving 3-(4-ethenylphenyl)thiophene (St-D).…”
Section: Synthesis Of Donor and Acceptor Monomersmentioning
confidence: 99%
“…Here, we present a proof of concept of the synthetic methodology leading to alternating D-A PB by using surface-initiated reversible-deactivation radical polymerization technique of the alternatingly polymerizable monomers. Styrene and maleic anhydride derivatives were used, as they are known for their tendency toward alternating copolymerization [45]. Thiophene (electron donor) and benzothiadiazole (electron acceptor) were attached to styrene and maleic anhydride, respectively, and the copolymer brushes were formed using surface-initiated RAFT polymerization and metal-free ATRP.…”
Section: Introductionmentioning
confidence: 99%
“…Although the synthesis of alternating copolymers by chain-growth mechanisms is rather limited, the radical copolymerization of styrene and maleic anhydride (MAn) is a conventional example. The non-homopolymerizable character of MAn and the favorable cross-propagation of a styryl radical with MAn resulted in the formation of an alternating copolymer . Thus, it has been demonstrated that non- or negligible homopolymerizability of the monomer plays an important role in the synthesis of alternating sequences via various polymerization mechanisms such as radical, , cationic, group transfer polymerization, and ring-opening metathesis polymerization. , In these cases, alternating copolymers are synthesized by suitably designing the reactivity of the monomers by tuning important factors such as the chemical structure, electron density, steric hindrance, and ring strain.…”
Section: Introductionmentioning
confidence: 99%